2014
DOI: 10.1007/s00330-014-3164-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial blood flow using dynamic 320-row multi-detector CT as compared with 15O-H2O PET

Abstract: Objectives: This study introduces a method to calculate myocardium blood flow (MBF) and coronary flow reserve (CFR) using the relatively low-dose dynamic 320-row multi-detector computed tomography (MDCT), validates the method against 15 O-H 2 O positron-emission tomography (PET) and assesses the CFRs of coronary artery disease (CAD) patients.Methods: Thirty-two subjects underwent both dynamic CT perfusion (CTP) and PET perfusion imaging at rest and during pharmacological stress. In 12 normal subjects (pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 37 publications
(12 reference statements)
0
70
0
2
Order By: Relevance
“…Most of these were performed in a limited number of patients and using different scanner generations, showing high sensitivity and negative predictive value, and moderate specificity and positive predictive value. Newer single center studies have shown improved positive predictive value as well as specificity, being validated by two large multicenter trials (43)(44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these were performed in a limited number of patients and using different scanner generations, showing high sensitivity and negative predictive value, and moderate specificity and positive predictive value. Newer single center studies have shown improved positive predictive value as well as specificity, being validated by two large multicenter trials (43)(44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the study population (22 out of 51) was compared to 15 O-H 2 O positron emission tomography (PET). 15 O-H 2 O allows for free diffusion (100 % extraction fraction) and is linearly correlated with myocardial uptake [27,28].…”
Section: Ct-mpi In Non-obstructive Cad and Microvascular Diseasementioning
confidence: 99%
“…CFR is now available noninvasively on multimodalities such as dynamic CT or MRI perfusion scan (15,16), SPECT (17), and flow velocity on MRI (18). The cold pressor test (CPT) is another method for stress testing in addition to adenosine stress.…”
Section: Future Directions and Alternativesmentioning
confidence: 99%